Virtual Learning in Higher Education: Students’ Perspectives from Mid-West University - Sharma, Chhabita; Khanal, Shanti Prasad (Spectrum of Humanities and Social Sciences, 2025)
This study explores the strengths, weaknesses, opportunities, and challenges of virtual learning experienced by students in the stream of Humanities and Social Sciences at a University during the COVID-19 pandemic. Employing a cross-sectional research design, data were collected through a self-administered questionnaire. The study population includes students enrolled in compulsory English courses across four campuses, with 159 participants selected via purposive sampling. SPSS was used for statistical analysis. Key strengths identified include flexibility, technological engagement, and adaptability, while challenges encompass confusion, lack of concentration, distractions, and technical skill deficiencies. Opportunities involve digital literacy development, innovative learning methods, and enhanced collaboration. However, technological barriers such as poor network connectivity, inadequate ICT infrastructure, lack of digital competency, and unclear policies significantly hinder learning effectiveness. The findings emphasize the need for comprehensive strategies to optimize virtual learning by addressing its multifaceted aspects at Mid-West University during and beyond the pandemic.